Методи та засоби збору і опрацювання даних в системах управління енергоефективністю підприємства - Теслюк, Тарас Васильович (Національний університет "Львівська політехніка", 2019)
В дисертаційній роботі розв’язанню важливе наукове завдання – розроблення та вдосконалення методів та засобів, які забезпечують підвищення ефективності збору і опрацювання даних в багаторівневих системах управління енергоефективністю підприємства. Розроблено моделі для дослідження динаміки функціонування засобів інформаційної технології збору і опрацювання даних в БСУЕП, які за рахунок використання теорії простих, кольорових та ієрархічних мереж Петрі забезпечують прийняття рішення про відповідність функціонування системи згідно з вимогами технічного завдання. Для розв’язання задачі структурного синтезу засобів збору і опрацювання даних в БСУЕП вдосконалено метод, який, на відміну від існуючих, за рахунок врахування інтерфейсів зв’язку між базовими складовими та їх параметрів, вимог технічного завдання та використанню інтегрального критерію забезпечує зменшення апаратно-часових затрат та синтез засобів БСУЕП. Вдосконалено метод безконфліктного обміну даними між складовими БСУЕП, який за рахунок узгодження інтенсивності надходження даних з інтенсивністю доступу до засобів обміну забезпечує визначення мінімальної швидкодії пам’яті для синтезу засобів обміну в реальному. Вдосконалено метод реалізації інтелектуальних засобів опрацювання даних з використанням нейромереж, який грунтується на паралельному таблично-алгоритмічному обчисленні скалярного добутку з використанням двох і більше таблиць та забезпечує зменшення часу опрацювання даних. В диссертационной работе решена важная научная задача - разработка и усовершенствование методов и средств, обеспечивающих повышение эффективности сбора и обработки данных в многоуровневых системах управления энергоэффективностью предприятия (МСУЭП). Разработаны модели для исследования динамики функционирования средств информационной технологии сбора и обработки данных в МСУЭП, которые за счет использования теории простых, цветных и иерархических сетей Петри обеспечивают принятие решения о соответствии функционирования системы с требованиями технического задания. Для решения задачи структурного синтеза средств сбора и обработки данных в МСУЭП усовершенствован метод, который, в отличие от существующих, за счет учета интерфейсов связи между базовыми составляющими и их параметрами, требований технического задания и использования интегрального критерия обеспечивает уменьшение аппаратно-временных затрат и синтез средств МСУЭП. Усовершенствован метод бесконфликтного обмена данными между составляющими МСУЭП, который за счет согласования, интенсивности поступления данных с интенсивностью доступа к средствам обмена, обеспечивает определение минимального быстродействия памяти для синтеза средств обмена в реальном. Усовершенствован метод реализации интеллектуальных средств обработки данных с использованием нейронных сетей, основанный на параллельном таблично-алгоритмическом исчислении скалярного произведения с использованием двух и более таблиц и обеспечивает уменьшение времени обработки данных. In the dissertation work the important scientific task is solved – development and improvement of methods and means that provide efficiency increasing of data collection and processing in multilevel energy efficiency management systems of the enterprise (MEEMSE). In the first chapter, information technologies of data collection and processing in multilevel energy efficiency management systems of the enterprise was analyzed and main directions of hardware and software development for synthesis of data collection and processing systems at the enterprise were established, that allowed to formulate the tasks of the dissertation research. In the second chapter, the method of synthesis of data collection and processing in energy efficiency management systems of the enterprise was improved, which provides reduction of hardware and time costs from 10 to 40% and synthesis of multi-level systems with high technical and economic indicators by mainstreaming interfaces, requirements of the specification. Method of non-conflict data exchange was built, which provides the definition of minimum memory performance for the synthesis of real-time exchange means by taking into account adjustment of intensity of data flow with intensity of access to means of exchange that reduces the cost of exchange means and energy consumption. Storage and sharing device of the MEEMSE with the industrial network was designed, which provides non-conflict data exchange in real time and increased the number of external devices, that realize many-to-many data model. The method of calculating the signal of post-synaptic excitation of neural elements in artificial neural networks, which is based on the parallel table-algorithmically calculation of scalar product with using two and more tables and provides reduction in two or more times the processing of technological data. In the third chapter, three-level basic architecture of MEEMSE with variable equipment composition was developed, which has permanent kernel and variable modules with the help of which adaptation of the system to the requirements of a particular enterprise is provided. Models of dynamic analysis of the means functioning of information technology of data collection and processing in multilevel energy efficiency management systems of the enterprise were built. Models based on theory of simple, color and hierarchical Petri nets provide a decision on the conformity of the functioning of the system in accordance with the requirements of the specification. Results of the analysis of developed net were represent in the form of graphs of the reach of states. The obtained results allow us to confirm that all the states are achievable, the network is alive, and dead ends are absent. In the forth chapter of dissertation work, the structure of information technology of data collection and processing in MEEMSE was developed. The structure, software and information support of synthesis system of means of of information technology of data collection and processing in MEEMSE were built, that allows to automate the synthesis process. The structure, software and technical support of tool of data collection and processing, which uses the model of artificial neural networks and provides the intellectualization of the functions of the device are given. The results of synthesis of data processing tool in MEEMSE and research of dependencies of time costs in the process of solving the problem of structural synthesis were presented.
Методы и средства сбора и обработки данных в системах управления энергоэффективностью предприятия
Methods and means of data collection and processing in energy efficiency management system of the enterprise
Keywords: інформаційна технологія; кольорові та ієрархічні мережі Петрі; метод синтезу з вказуванням інтерфейсів; метод безконфліктного обміну даними; метод побудови інтелектуальних засобів опрацювання даних; информационная технология; цветные и иерархические сети Петри; метод синтеза с учетом интерфейсов; метод бесконфликтного обмена данными; метод построения интеллектуальных средств обработки данных; information technology; hierarchical and colored Petri nets; synthesis method based on interfaces; method of non-conflict data exchange; method of constructing intelligent data processing means; 004.[9+896]